HVSR Microtremor Resonance Frequency and Amplification Analysis Using Earthquake Data for Seismic Hazard Mitigation in Lombok Island - Mohammad Syamsu Rosid; Sigit Pramono; Frilla Renty Tama Saputra; Daryono Daryono; Setyoajie Prayoedhie; Edy Santoso (Diponegoro University Semarang Indonesia, 2026)
Lombok Island exhibits high seismicity driven by the complex interaction between the subduction of the Indo-Australian plate beneath the Eurasian plate and the activity of the Flores Back-arc Thrust. In seismic hazard mitigation, the Horizontal-to-Vertical Spectral Ratio (HVSR) technique is a fundamental tool for estimating site effects. However, the validity of parameters derived from ambient noise (MHVSR) versus earthquake records (EHVSR) remains a subject of geophysical debate, particularly in regions with high structural heterogeneity. This research evaluates the reliability of resonance frequency (f0) and amplification factor (A0) by conducting a direct comparison between MHVSR and EHVSR datasets. Seismic data from seven BMKG stations across Lombok were meticulously selected and processed. The analysis involved windowing and the application of Fast Fourier Transform (FFT) to transition raw waveforms into the frequency domain, allowing for the extraction of stable HVSR spectral curves. The findings reveal a robust correlation between microtremor and earthquake-derived HVSR, with on f0 (r = 0.9954, σ = 0.301) and A0 (r = 0.9232, σ = 0.75). Observed minor discrepancies are likely the result of local lithological conditions, wave attenuation, and source-dependent variations such as magnitude or hypocentral distance. Ultimately, this study confirms that ambient vibration HVSR provides dependable estimates of site resonance parameters, aligning with earthquake records within tolerable error margins. These results strengthen the case for microtremor investigations as a reliable, non-invasive method for local seismic hazard evaluation. Such findings are vital for refining seismic hazard mitigation and enhancing urban resilience planning in seismically active zones like Lombok island.